Delays in diagnosis and treatment of depressive disorder among young adults: A national online survey-based cross-sectional study - Rena Xu; David Pletta; Caitlynn Feng; Cassandra Morrow; Maya C. Clark; Badar Omar; Alex S. Keuroghlian; Sari L. Reisner (PLoS ONE, 2026)
Background Depression is highly prevalent among U.S. young adults and associated with long-term functional impairment and increased suicide risk. While delays in diagnosis and treatment of depression are well documented among older adults, the magnitude and predictors of such delays in the younger population are poorly understood. Objective To characterize the time to diagnosis and treatment of depressive disorder and predictors of diagnostic and treatment delay among young adults. Methods This cross-sectional study used a self-reported survey conducted via the online research platform Prolific in May 2025. Eligible participants were U.S. adults aged 18–35 years with a history of at least one depressive episode. Sociodemographic, clinical, and psychosocial characteristics, including age of depressive symptom onset, degree of social support, and frequency of social group engagement, were assessed. Primary outcomes were probability of not receiving a depressive disorder diagnosis despite symptoms, time from symptom onset to diagnosis, probability of not seeking treatment, and time from symptom onset to treatment. Secondary outcomes were perceived treatment effectiveness and current symptom control. Results In total, 871 respondents met inclusion criteria. Of those with one or more lifetime depressive episodes, 46.2% reported never receiving a depressive disorder diagnosis. Median time from symptom onset to diagnosis was 3 years (IQR: 0–7). Over a quarter (27.4%) never sought treatment; among those who did, 93.5% received care, but 31.4% experienced a delay of 1–4 years, and 28.8% experienced a delay of 5 + years. Symptom onset in childhood (ages 0–12) or adolescence (ages 13–17) was associated with longer time to diagnosis and treatment and lower perceived treatment effectiveness. Greater social support was associated with shorter time to diagnosis; lower probability of never receiving a diagnosis, never seeking treatment, or experiencing prolonged treatment delay; and higher perceived treatment effectiveness and current symptom control. Frequent engagement in social groups was also associated with greater perceived treatment effectiveness. Conclusions Among U.S. young adults, prolonged delays in depression diagnosis and treatment are common. Early symptom onset is associated with longer delays and worse outcomes, whereas greater social support is associated with shorter delays and more favorable outcomes. These findings highlight the need for further research to clarify causal mechanisms and for interventions to promote timely diagnosis and treatment among young adults at risk for depression.